THE HEBREW BIBLE AND METAETHICS: A PHILOSOPHICAL INTRODUCTION - Gericke, Jaco (Scriptura, 2010)
In the discipline of Biblical Ethics (Hebrew Bible) the concern lies with descriptive and normative ethics whereas questions pertaining to metaethics are frequently bracketed. As a result, very little attention has been paid to the semantic, epistemological and metaphysical assumptions underlying in the Hebrew Bible's moral discourse. In response to this state of affairs, this paper seeks to make a plea for the introduction of metaethics within the field of Biblical Ethics by demonstrating how this line of inquiry can be simultaneously philosophical and hermeneutically valid in terms of research problems, objectives and methodology. The study concludes with a cursive introduction to three interesting metaethical problems in connection with biblical assumptions regarding the divinity-morality relation when viewed from the perspective of the Euthyphro Dilemma, the Principle of Sufficient Reason and the question of morality and meaning in the divine condition.